Kajian Lingkungan dari Potensi Pembangkit Listrik Tenaga Surya di Energy Park Universitas Proklamasi 45 - Daniel Kurniawan; Andri Prasetyo Nugroho; M. Noviansyah Aridito; Trisno Fallo (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
Indonesia is a country that is located right on the equator. This is certainly very supportive of one of the accelerations of Solar Power Plants. Proklamasi 45 University as a university in Yogyakarta that focuses on renewable energy plans to build an energy-themed location within the campus environment, named “Energy Park” with grid-connected Solar Power Plants as a source of electrical energy. This research aims to calculate the potential for electrical energy, its contribution to reducing CO2 emissions, and the feasibility of the Energy Park project from an economic point of view. The method used in this research is comparing data in the field and the system simulation method with PVsyst software as well as cash-flow analysis calculations. According to the results of the system simulation, the potential for electrical energy generated by rooftop grid-connected PV mini-grid each year is calculated at 8,310 kWh or 8.31 MWh, with details per kWp of 1528 kWh/kWp/year. Then the contribution of reducing CO2 emissions from the implementation of Energy Park’s Solar Power Plants with electricity production of 8.31 MWh/year for 30 years is 148,2 tCO2. Through cash-flow analyst calculations, it is known that the Energy Park’s Solar Power Plants project is not economically feasible when referring to the current selling price of electrical energy and the performance of the existing Energy Park’s Solar Power Plants.